PENGARUH KONSELING KELOMPOK GESTALT TEKNIK REVERSAL DAN TEKNIK STAYING WITH THE FEELING UNTUK MENINGKATKAN KEAKTIFAN ORGANISASI - Suciati, Kurnia; Japar, Muhammad; Kurniati, Astiwi (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
This study aims to examine the effect of group counseling with the Reversal Technique and the Staying With The Feeling technique to improve the organization of adolescents.This study uses a design using the pretest-posttest control group design method. The samples taken in the study were 12 people consisting of 6 experimental group 1 with the Reversal Technique and the experimental group 2 with the Staying With The Feeling Technique. Sampling using random sampling technique. The method of data collection was carried out using a questionnaire on organizational activity. The data analysis method used the One Way Annova Parametric Statistical Test.The results of this study indicate that group counseling with the Reversal Technique and the Staying With The Feeling technique are effective in increasing organizational activity in adolescents. This is evidenced by the results of the One Way Annova Parametric Statistics test with a probability significance value of .001. Based on the results of the analysis and discussion, there are differences in the average score of the two groups' organizational activity questionnaires. The experimental group 1 had an increase of 22.38% while the experimental group 2 had an increase of 1.56%. The conclusion in this study is that group counseling with the Reversal Technique is more influential in increasing organizational activity than group counseling with the Staying With The Feeling Technique.